2017
DOI: 10.1021/acs.jpcc.7b07243
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Photocatalytic Hydrogen Evolution on Band Structure Tuned Polytriazine/Heptazine Based Carbon Nitride Heterojunctions with Ordered Needle-like Morphology Achieved by an In Situ Molten Salt Method

Abstract: Polymeric carbon nitride (CN) is a fascinating metal-free photocatalyst for active solar energy conversion via water splitting. However, the photocatalytic activity of CN is significantly restricted by the intrinsic drawbacks of fast charge recombination because of incomplete polymerization. Herein, an in situ ionothermal molten salt strategy has been developed to construct polytriazine/heptazine based CN isotype heterojunctions from low cost and earth-abundant urea as the single-source precursor, with the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 62 publications
4
34
0
4
Order By: Relevance
“…It was demonstrated that increasing the synthesis temperature from 500 to 550 °C resulted in the changes in phase structure from heptazine-based units (amorphous CN) to poly(triazine imide) (crystalline CN) with high crystalline phase, owing to its high thermal stability compared to amorphous CN at high temperature in the presence of molten salts. Similar results on the changes of the crystallinity phase were also reported on crystalline CN prepared by urea-based precursor when temperature variation was carried out [27]. The presence of the amorphous phase at a high temperature (600 °C) might be related to the binary phase properties of KCl-LiCl.…”
Section: Effect Of Synthesis Temperaturesupporting
confidence: 79%
“…It was demonstrated that increasing the synthesis temperature from 500 to 550 °C resulted in the changes in phase structure from heptazine-based units (amorphous CN) to poly(triazine imide) (crystalline CN) with high crystalline phase, owing to its high thermal stability compared to amorphous CN at high temperature in the presence of molten salts. Similar results on the changes of the crystallinity phase were also reported on crystalline CN prepared by urea-based precursor when temperature variation was carried out [27]. The presence of the amorphous phase at a high temperature (600 °C) might be related to the binary phase properties of KCl-LiCl.…”
Section: Effect Of Synthesis Temperaturesupporting
confidence: 79%
“…Furthermore, the detailed microstructure of CN, CN‐0.20%Dx and CN‐0.20%Dx‐25 were analyzed by TEM, which are shown in Figure a‐c. CN‐0.20%Dx‐25 presents uniform, needle‐like nanorods structure that are formed in a random orientation way (Figure c), which is different with previous report . It can be also found that the morphology of CN‐25 is similar to that of CN‐0.20%Dx‐25.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the PL spectra of doped CN photocatalysts excited at 325 nm. The strong PL intensity of samples indicates that the fast recombination degree of photogenerated electron–hole pairs . Thus, the significant decrease of PL intensity of doped CN photocatalysts is observed, suggesting that the introduction of S (Figure a) and K (Figure b) can reduce the recombination rate of photogenerated electron–hole pairs.…”
Section: Resultsmentioning
confidence: 99%
“…Puncak tertinggi menunjukkan 2θ = 27.4° pada puncak (002) mempamerkan pembelauan struktur grafitik dengan jarak d= 0.326 nm seperti yang dilaporkan oleh Peng et al (2016). Selain itu, puncak 2θ = 13.3° mewakili puncak pembelauan (100) menunjukkan unit bagi triazine (Jin et al 2017;Safaei et al 2018). Kedua-dua puncak ini menunjukkan g-C 3 N 4 telah berjaya disintesis daripada urea dan dilarutkan dengan pelarut metanol sebelum disinarkan dengan nilai dos 0.1 kGy dan 0.5 kGy.…”
Section: Keputusan Dan Perbincangan Komposisi Dan Kehabluranunclassified
“…Manakala puncak gelombang pada nilai 1241 cm -1 , 1408 cm -1 dan 1630 cm -1 merujuk kepada mod regangan heterosikel C-N. Ini merujuk kepada pembentukan jaringan sambungan bagi ikatan C-N-C untuk struktur g-C 3 N 4 (Wang et al 2012). Pada puncak gelombang lebar antara 3000 cm -1 hingga 3600 cm -1 menghubungkan regangan N-H bagi kumpulan amina sekunder dan amina primer dengan unit s-triazine (Jin et al 2017;Peng et al 2016).…”
Section: Analisis Perubahan Struktur Kimiaunclassified